2009
DOI: 10.1002/pola.23633
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of three‐dimensional poly(dimethylsiloxane) (PDMS) with movable cross‐linking

Abstract: A pentamethylcyclotrisiloxane moiety was introduced into cyclic polystyrene (cPSt) and cyclic PDMS (cPDMS) to obtain noncovalent cross‐linking agents, D3‐cPSt and D3‐cPDMS, respectively. Anionic ring‐opening polymerization of octamethylcyclotetrasiloxane (D4) in nitrobenzene was carried out in the presence of D3‐cPSt to obtain a cloudy white PDMS gel as a precipitation. On the other hand, bulk copolymerization of D3‐cPDMS with D4 proceeded in a homogeneous state to give a colorless transparent PDMS gel in high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Because the fabrication method involves the “assembly” of individually formed components as if they are mosaics or toy blocks, we first prepared the stretchable electrodes and composite pieces separately. PDMS was used as the substrate for the stretchable electrode because of its high light transmittance, biocompatibility, chemical stability, and excellent elasticity. , PEDUB, by itself, is freestanding and has high ductility, but it is not suitable as a substrate for stretchable devices due to its low strength and poor resilience after stretching. However, the surface of pristine PDMS is known to be intrinsically hydrophobic, which restricts its use as a substrate for the deposition of another material.…”
Section: Resultsmentioning
confidence: 99%
“…Because the fabrication method involves the “assembly” of individually formed components as if they are mosaics or toy blocks, we first prepared the stretchable electrodes and composite pieces separately. PDMS was used as the substrate for the stretchable electrode because of its high light transmittance, biocompatibility, chemical stability, and excellent elasticity. , PEDUB, by itself, is freestanding and has high ductility, but it is not suitable as a substrate for stretchable devices due to its low strength and poor resilience after stretching. However, the surface of pristine PDMS is known to be intrinsically hydrophobic, which restricts its use as a substrate for the deposition of another material.…”
Section: Resultsmentioning
confidence: 99%
“…43 They were subsequently applied to construct more complex polymer topologies either through the covalent linkage or even through the noncovalent, mechanical linkage uniquely formed by threading with ring polymer units. 44,45 It was also shown that network polymers formed from cyclic polymer precursors exhibited unique gel properties compared with conventional gels obtained with linear/ branched polymer precursors. 46 Moreover, the topological conversion of polymers between ring/linear and even between single-cyclic/dicyclic topologies has now been achieved.…”
Section: Synthetic Developments For Single-cyclic (Ring) and Multi-cy...mentioning
confidence: 99%
“…These isolated rings can be extracted by chloroform. On the other hand, a network connected by topological crosslinks, such as a rotaxane-crosslinked elastomer, is known to swell significantly in good solvents due to the inherent chain slipping [30]- [33]. Although the concatenated ring elastomer and the rotaxane-crosslinked elastomer are not exactly identical in terms of their molecular structures, they both possess movable linkages, which may allow the superior swelling ratio of 45 of the concatenated ring elastomer investigated herein.…”
Section: Long-term Swelling Experimentsmentioning
confidence: 97%